اتجاهات النخبة نحو التغطية الإعلامية لقناة الجزيرة حول قضية طوفان الأقصى - معمري,أماني; داسي,اسيا; كرطي,الحبيب (University of Eloued جامعة الوادي, 2024)
This study aimed to find out the public trends towards the media coverage of Al Jazeera about the Al-Aqsa flood issue. we conducted a field study on a sample of professors from Hama al-Akhdar al-Wadi University, and we relied on the survey methodology aimed at recording, analyzing and interpreting the phenomenon, and from the study tools, we touched on the use of questionnaire and observation, and the sample was estimated at(100) university professors at martyr Hama Lakhdar University in Wadi, who in turn answered the questionnaire, the study: - There are many customs and patterns for the university professors at the University of martyr Hama Lakhdar in the valley to show Al Jazeera - The interest of the university professors of the martyr Hama Lakhdar University in the valley to follow up the issue of the Al-Aqsa flood is high. - Sample study their positive attitudes towards the media coverage of Al Jazeera about the issue of the Al-Aqsa flood
Keywords: طوفان الأقصى; التغطية الإعلامية; قناة الجزيرة; Al Aqsa flood; media coverage; Al Jazeera